Effect of expander extruder processing on nutritive value of maize cobs based complete diet of buffaloes - REDDY, G V N; REDDY, K JOJI (The Indian Journal of Animal Sciences, 2013)
Expander-extruder processed maize cobs (40%) based complete diet, corresponding mash diet and a conventional diet (containing concentrate mixture and ground-maize cobs in 60: 40 ratio as in complete diets i e as such basis) were fed to 3 permanently fistulated male buffaloes using 3 x3 latin square design to assess the effeet ofthese diets on rumen fermentation pattern and nutrient utilization. The DMI and water intake/kg DMI were comparable on all the diets. Total N, TCA-precipitable N and residual N were increased (P